Bilateral Acute Macular Neuroretinopathy (AMN) after COVID-19 and its Clinical Course - Bartsch, Alexander; Skornia, Adam; Mardin, Christian Y.; Hohberger, Bettina (Klinische Monatsblätter für Augenheilkunde, 2023)
Acute macular neuroretinopathy (AMN) is a rare disease entity. It is mainly observed in young women with a history of influenza-like infection or who have been taking oral contraceptives for several years. Patients typically describe subjective visual deterioration and mono- or bilateral paracentral relative scotomas. In some cases, funduscopic ophthalmic examination may reveal subtle sharply demarcated flat lesions of reddish-brown or orange colour in the macular region. Diagnosis is usually made by near-infrared fundus imaging which shows hyporeflective areas, and SD-OCT imaging which manifests changes in the outer retinal layers. In the following, three patient cases with bilateral AMN are described which occurred in direct temporal relationship to a recent SARS-CoV-2 infection.
CRIS-Team WoS Importer:2023-06-02
Keywords: akute makuläre; Neuroretinopathie; SD-OCT; Retina; COVID-19; SARS-CoV-2

Drug- and Cell-Type-Specific Effects of ROCK Inhibitors as a Potential Cause of Reticular Corneal Epithelial Edema - Schlötzer-Schrehardt, Ursula; Gießl, Andreas; Zenkel, Matthias; Bartsch, Alexander; Okumura, Naoki; Koizumi, Noriko; Kinoshita, Shigeru; Tourtas, Theofilos; Kruse, Friedrich (Cells, 2025)
Rho-associated kinase (ROCK) inhibitors have gained popularity as novel treatment options in the management of glaucoma and corneal endothelial disorders. Among the various ocular side effects, reticular corneal epithelial edema has been most frequently reported, mainly after treatment with netarsudil. To explain the potential mechanisms, we comparatively analyzed the effects of ripasudil and netarsudil on corneal endothelial and epithelial function in vitro. Primary human corneal endothelial and epithelial cells were incubated with netarsudil dihydrochloride and ripasudil hydrochloride dihydrate for up to 7 days. Gene and protein expression analyses were performed by real-time PCR and immunocytochemistry. Functional assays assessed the cell migration, proliferation, viability, Na+/K+-ATPase activity, transcellular electrical resistance, and FITC–dextran permeability. Reticular bullous corneal epithelial edema was observed in a patient following netarsudil 0.02%/latanoprost 0.005% ophthalmic solution (Roclanda®) for elevated intraocular pressure. In the subsequent laboratory analyses, both netarsudil and ripasudil were found to improve the corneal endothelial pump and barrier function, but they showed differential effects on corneal epithelial cells. Whereas ripasudil improved the epithelial barrier function by upregulating major components of the tight and adherens junctions and reducing paracellular permeability, netarsudil had no or even adverse effects on the epithelial barrier properties by downregulating the expression levels of cell-junction-associated genes. The expression changes normalized after discontinuation of ROCK inhibitors. The findings support the concept that ROCK inhibitors can act as a double-edged sword by having beneficial effects on corneal endothelial cells and adverse effects on epithelial cells.
CRIS-Team Scopus Importer:2025-03-14
Keywords: corneal endothelium; corneal epithelium; honeycomb epithelial edema; netarsudil; reticular bullous corneal epithelial edema; Rho kinase inhibitor; ripasudil; ROCK inhibitor

Post-COVID-19 Syndrome: Retinal Microcirculation as a Potential Marker for Chronic Fatigue - Schlick, Sarah; Lucio, Marianna; Wallukat, Gerd; Bartsch, Alexander; Skornia, Adam; Hoffmanns, Jakob; Szewczykowski, Charlotte; Schröder, Thora; Raith, Franziska; Rogge, Lennart; Heltmann, Felix; Moritz, Michael; et al. (International Journal of Molecular Sciences, 2022)
Post-COVID-19 syndrome (PCS) is characterized by persisting sequelae after infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). PCS can affect patients with all COVID-19 disease severities. As previous studies have revealed impaired blood flow as a provoking factor triggering PCS, it was the aim of the present study to investigate the potential association between self-reported chronic fatigue and retinal microcirculation in patients with PCS, potentially indicating an objective biomarker. A prospective study was performed, including 201 subjects: 173 patients with PCS and 28 controls. Retinal microcirculation was visualized by OCT angiography (OCT-A) and quantified using the Erlangen-Angio-Tool as macula and peripapillary vessel density (VD). Chronic fatigue (CF) was assessed according to the variables of Bell’s score, age and gender. VDs in the superficial vascular plexus (SVP), intermediate capillary plexus (ICP) and deep capillary plexus (DCP) were analyzed, considering the repetitions (12 times). Seropositivity for autoantibodies targeting G protein-coupled receptors (GPCR-AAbs) was determined by an established cardiomyocyte bioassay. Taking account of the repetitions, a mixed model was performed to detect possible differences in the least square means between the different groups included in the analysis. An age effect in relation to VD was observed between patients and controls (p < 0.0001). Gender analysis showed that women with PCS showed lower VD levels in the SVP compared to male patients (p = 0.0015). The PCS patients showed significantly lower VDs in the ICP as compared to the controls (p = 0.0001 (CI: 0.32; 1)). Moreover, considering PCS patients, the mixed model revealed a significant difference between those with chronic fatigue (CF) and those without CF with respect to VDs in the SVP (p = 0.0033 (CI: −4.5; −0.92)). The model included variables of age, gender and Bell’s score, representing a subjective marker for CF. Consequently, retinal microcirculation might serve as an objective biomarker in subjectively reported chronic fatigue in patients with PCS.
CRIS-Team Scopus Importer:2022-12-09
Keywords: chronic fatigue; chronic fatigue syndrome; COVID-19; functional GPCR autoantibodies; long COVID syndrome; OCT angiography; post-COVID-19 syndrome; retinal microcirculation